Land Grabbing and International Political Economy: Towards a Critical Neo-Gramscian Theoretical Model of Land Governance in Latin America - Mora, Sol Yamila (2022)
The vigorous debate on global land grabbing within Critical Agrarian Studies contrasts with the incipient analyses from International Political Economy (IPE). This divergence has overshadowed the multi-scalar nature of the power relations that shape land governance, and consequently its effects on land grabbing. For this reason, this paper provides a critical theoretical model of land governance based on Robert Cox?s historical structures approach to understand the causes of land grabbing in Latin American countries. It is argued that this model renders visible the articulation of the local and global processes driving land grabbing because it foregrounds the power relations at multiple scales that shape decisions on land access, use and control, as well as the conflicts inherent to them. This demonstrates that, on the one hand, land governance structures in Latin America play a hegemonic role since they express and develop the global agricultural model that promotes land grabbing. On the other hand, social resistance highlights that land governance simultaneously possesses a potential for change. As a result, the knowledge about land grabbing is enhanced through dialogue between the two fields of study.